2021
DOI: 10.1007/s12325-021-01704-y
|View full text |Cite
|
Sign up to set email alerts
|

Mortality in Patients with COVID-19 on Renin Angiotensin System Inhibitor Long-Term Treatment: An Observational Study Showing that Things Are Not Always as They Seem

Abstract: Introduction At the beginning of the coronavirus disease 2019 (COVID-19) pandemic, controversial data were reported concerning angiotensin-converting enzyme (ACE) inhibitors and angiotensin II receptor blockers (ARBs) that induced a number of physicians to stop using them in patients with COVID-19. Although large-scale studies have ruled out this concern, it is common experience that patients with COVID-19 taking ACE inhibitors or ARBs are at increased risk of death. The aim of this study was to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
(22 reference statements)
0
2
0
1
Order By: Relevance
“…The systematic search identified 169 observational studies that assessed the associations between RAAS inhibitor use and the risk of contracting a SARS‐CoV‐2 infection and/or experiencing severe COVID‐19 outcomes (Figure 1 ). 8 , 19 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , …”
Section: Resultsmentioning
confidence: 99%
“…The systematic search identified 169 observational studies that assessed the associations between RAAS inhibitor use and the risk of contracting a SARS‐CoV‐2 infection and/or experiencing severe COVID‐19 outcomes (Figure 1 ). 8 , 19 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , …”
Section: Resultsmentioning
confidence: 99%
“…However, most of the reviewed studies were not exclusively examining a T2D population, and limited prospective evidence on this topic remains. It has also been suggested that there may be an increased risk of COVID-19 mortality associated with patients receiving long-term treatment with ARBs that is due to the conditions associated with their use, including diabetes, rather than the drugs themselves [ 39 ]. Future research is needed that directly accounts for duration of T2D in the context of medication class effects.…”
Section: Discussionmentioning
confidence: 99%
“…У нашому дослідженні у пацієнтів, які приймали іАПФ, порівняно з пацієнтами, які приймали БРА, спостерігалася тенденція до меншої потреби у кисневій терапії, хоча статистично при цьому достовірної різниці не встановлено (р=0,07). У дослідженні, в якому порівнювали летальність та важкість перебігу коронавірусної хвороби COVID-19 у пацієнтів, які приймали іАПФ, та у пацієнтів, які приймали БРА, не виявлено суттєвої різниці у цих показниках [11].…”
Section: (22) квітень-червень 2022unclassified